Rapid Post-uterine Involution in Dairy Cows: Mechanisms, Dietary Strategies, and Impact on Postpartum Recovery - Emran Hossain; Shilpi Islam (Emerging Trends in Metabolites, 2025)
The postpartum period in dairy cows is critical for reproductive success, with uterine involution playing a central role in returning the reproductive tract to its pre-pregnancy state. Rapid uterine involution is essential for improving reproductive performance and minimizing the risk of postpartum complications. This review explores the nutritional mechanisms that influence uterine involution, focusing on key dietary strategies to promote tissue repair and recovery. We examine the role of energy, protein, minerals, vitamins, and fatty acids in supporting uterine health and accelerating involution. Additionally, the interplay between gut health, oxidative stress, and hormonal regulation is discussed in the context of nutrient-driven recovery. Furthermore, we highlight the effects of dietary modifications on inflammation control, uterine muscle function, and immune response, all of which contribute to faster involution and improved fertility outcomes. By synthesizing current research, this review provides a comprehensive overview of how strategic nutritional interventions can optimize postpartum recovery, enhance uterine health, and improve overall reproductive efficiency in dairy cows.
Keywords: Cow; energy balance; fatty acids; minerals; postpartum recovery; reproductive health; trace elements; uterine involution